Pengembangan LKPD berbasis Model Pembelajaran RME dengan Pendekatan Saintifik untuk Meningkatkan Kemampuan Komunikasi Matematis - Selvia Lovita; Caswita Caswita; Undang Rosidin (Mandalika Mathematics and Educations Journal, 2025)
This research is a type of Research and Development (R&D) that adapts the ADDIE model. This research aims to develop LKPD based on the RME model with a scientific approach that is valid, practical, and effective in improving students' mathematical communication skills. Data collection techniques were carried out through interviews, observations, questionnaires, and mathematical communication ability tests. The data collection instruments were interview guidelines, expert validation questionnaires, and response questionnaires. The research was conducted at the UPT SMPN 1 Pardasuka in the odd semester of the 2025/2026 academic year. The results showed that the developed LKPD met the criteria of being valid, practical, and effective. The effectiveness test results showed that LKPD based on the RME model with a scientific approach could improve mathematical communication skills. The average N-Gain score for the experimental class was 0.717, which is in the high category, while the control class scored 0.633, which is in the moderate category. The t-test results showed a significance value of 0.034 < 0.050, which means that there was a difference between the two classes. Therefore, it can be concluded that LKPD based on the RME model with a scientific approach is effective in improving students' mathematical communication skills.